Tafsir Konstitusionalitas terhadap Batas Usia Pemidanaan Anak - Hwian Christianto (The Constitutional Court of the Republic of Indonesia, 2016)
Child’s age limit acts is an absolute requirement which shall be notified in order to avoid him or her to be a victim. Acts No. 3, 1997 about Court of Children states that 8 (eight) years old as the limit and it can be proposed to. Of course this statement brings consequence to children growth’s rights and it is considered as a threat that he/she shall experience an hard law-process. On another hand, the decision of Supreme Court No. 1/PUU-VII/2010 answers this problem, by pulling up the application and deciding 12 years old as a new limit for the accused child. The regulation definitely brings a big change into child’s criminal law concept in Acts No. 3, 1997. The objection of law’s application as limitation for a child in the court also said by the applicant and considered as legality and human right trafficking.